1992
DOI: 10.1007/bf00176302
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the cytoadhesin integrins in the human cornea

Abstract: Cell-matrix interactions play a fundamental role in normal and pathological conditions. They can be mediated by the cytoadhesin subgroup of the integrin superfamily of adhesion molecules. Its members include the vitronectin receptor (VNR) and the platelet glycoprotein IIb/IIIa (GP IIb/IIIa). Both receptors are composed of an alpha-chain (alpha v and alpha IIb, respectively) coupled to a beta 3-chain. Using in situ immunohistochemistry and monoclonal antibodies, the authors studied the distribution of GP IIIa (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…The ligand specificity of the a6P4 complex is still unknown, but it appears to be a component of the hemidesmosome complex (Sonnenberg et al, 1991;Stepp et al, 1990). In contrast t o Lauweryns et al (1991) we found no immunoreactivity for a4 or a5 integrins in human corneal epithelium. The distribution of integrins in the cornea appears to differ from that of other stratified epithelia, at least in the presence of the a, integrin in the basal cells .…”
Section: Lntegrins In Stratified Epithelial Cells Including the Corneacontrasting
confidence: 97%
See 1 more Smart Citation
“…The ligand specificity of the a6P4 complex is still unknown, but it appears to be a component of the hemidesmosome complex (Sonnenberg et al, 1991;Stepp et al, 1990). In contrast t o Lauweryns et al (1991) we found no immunoreactivity for a4 or a5 integrins in human corneal epithelium. The distribution of integrins in the cornea appears to differ from that of other stratified epithelia, at least in the presence of the a, integrin in the basal cells .…”
Section: Lntegrins In Stratified Epithelial Cells Including the Corneacontrasting
confidence: 97%
“…The expression of integrins in the epidermis (Peltonen et al, 1989; Klein et al, 1990), gingiva (Hormia et al, 1990) and cornea (Lauweryns et al, 1991; has been studied in detail. In all of these epithelia, the p,, a, and a3 subunits are found in basal and suprabasal cells throughout the cell membrane, most likely serving to mediate cell-cell interactions (Fig.…”
Section: Lntegrins In Stratified Epithelial Cells Including the Corneamentioning
confidence: 99%
“…The peptide RGD (Arg‐Gly‐Asp) is a rational first choice as the bioactive ligand to be incorporated into PEG hydrogels to provide specific and relevant adhesion moieties to the HCECs because this sequence is involved in binding to cell substrate adhesion receptors including several integrins 23. In the cornea, the epithelial basal cells are in direct contact with the BM and exhibit high expression levels of the RGD‐binding α 5 β 1 integrin,24 and corneal epithelial cells migrating across a wound express α 5 β 1 integrin at increased levels 25, 26. In wound healing experiments in vitro using HCECs, the wound closure rate increased from 2 μm/h in the absence of RGD up to 10 μm/h with 80% RGD content 27.…”
Section: Introductionmentioning
confidence: 99%
“…12 My colleague Michael Davey and I have updated this speculation in an essay in Arthritis & Rheumatism. 13 The endotoxin-induced uveitis model has been useful for some of the initial publications on intraocular cytokines, 14,15 adhesion molecules, 16,17 complement, 18 and intracellular pathways 19 activated by a ligand for a toll receptor during inflammation within the eye. Like all animal models, however, this one has limitations.…”
mentioning
confidence: 99%